Heterogeneously Catalyzed Hydrogenation of Squalene to Squalane under Mild Conditions. Issue 14 (26th September 2014) - Pandarus, Valerica; Ciriminna, Rosaria; Kaliaguine, Serge; Béland, François; Pagliaro, Mario
Abstract The full chemoselective hydrogenation of highly unsaturated all‐trans linear squalene into valuable fully saturated squalane is achieved smoothly under mild conditions over the sol–gel‐entrapped Pd catalyst SiliaCat Pd0. The catalysis is truly heterogeneous, and the catalyst is stable and recyclable, which opens the route to an easier and less expensive hydrogenation of squalene.